Cybersecurity Risks to Developing States Security: A New Lens in Addressing the Non-Traditional Threats - Mat, Bakri; Wahid, Ratnaria; Keling, Faisol; Pero, Siti Darwinda; Ahmad, Fakhrorazi (UUM, 2021)
In the era of hyper connectivity and globalization, cyber security is an indispensable component of national security. Malaysia as a developing nation is presented with the new challenge in the cyber environment as well as the existing circumstances as a small state. In facing cyber threats, this research is designed to examine the theoretical role of cybersecurity as the encompassing non-traditional security element to national security framework of the developing states and understanding the existing mechanisms and awareness on cybersecurity. This research utilized observations and in-depth interviews of field experts and policymakers, as well as library study to qualitatively address the research problem. It is found that the model compartmentalizes our understanding of cyberthreat in national security framework. Various mechanisms, policies, and laws has been enacted in relation to cybersecurity in Malaysia, however there is still room for improvement in terms of holistic and law-binding acts. In general, the public are aware on the importance of cyber vigilance, but the rising statistics of fraud and scam showed that further scrutiny is required. The complexity of cybersecurity demands a comprehensive understanding. The effort of eradicating cyberthreats involve multiple government instruments and agencies, cooperation of private sectors, as well as members of the society. Therefore, this research recommended a model of small-state cybersecurity based on the works of Muthiah Alagappa.